The Impact of Behavioral Factors on Investment Decisions: Evidence from IT and ITES Employees in Chennai - Kavya, J.; Kotteeswaran, M. (Journal of Neonatal Surgery, 2025)
This study investigates the impact of behavioral factors—specifically risk tolerance, financial literacy, overconfidence, herd behavior, peer influence, and past investment experience—on the investment decision quality of employees in the IT and ITES sectors in Chennai, India. The research employs a quantitative approach, utilizing survey data collected from 261 employees within these industries. A multiple regression analysis was conducted to explore the relationships between the behavioral factors (independent variables) and investment decision quality (dependent variable). The results reveal that, while there were weak correlations between certain behavioral factors and investment decision quality, none of the independent variables were statistically significant predictors of investment decision quality. The only significant predictor in the regression model was the intercept, suggesting that other, unexamined factors may play a more influential role in shaping the investment decisions of IT and ITES employees. Additionally, the model’s low R-squared and Adjusted R-squared values indicate that the behavioral factors analyzed do not explain a substantial portion of the variation in investment decisions. Based on these findings, the study recommends enhancing financial literacy programs, providing tailored investment advice, and addressing psychological biases such as overconfidence. Further research is also suggested to explore additional factors influencing investment decisions, such as external financial advice, socio-economic status, and market knowledge. This study contributes to the behavioral finance literature by highlighting the complexities of investment decision-making and the limitations of common behavioral predictors in specific workforce sectors.